Evidence for the treatment of moderate depression: a systematic review. (15th June 2017) - Aherne, D.; Fitzgerald, A.; Aherne, C.; Fitzgerald, N.; Slattery, M.; Whelan, N.
Abstract : Objectives: This study aims to investigate existing evidence for the effectiveness of psychological treatments and/or antidepressant medication as a treatment for those diagnosed with moderate levels of depression. Methods: A PRISMA systematic review of articles using electronic research databases (2000–2014) was conducted to identify studies investigating the effectiveness of psychotherapy and/or medication as a treatment for people with moderate levels of depression. Search terms included moderate depression, psychotherapy and/or medication, depressive disorders, antidepressants, psychotherapy, mental health services, and randomized-controlled trial (RCT). The included studies were then assessed, extracted, and synthesised. Results: A total of 14 studies met the inclusion criteria (11 RCTs and three additional studies) for this review. The findings of the systematic review indicate that there is limited evidence available specific to the treatment of moderate depression and that this research seems to suggest that psychotherapy or combined treatment has a beneficial effect. Conclusions: Given that depression is one of the biggest challenges the world faces at present, further research is required to examine the effectiveness of treatment for different levels of depression severity.